Sucrose-preferring gut microbes prevent host obesity by producing exopolysaccharides - Hidenori Shimizu; Junki Miyamoto; Keiko Hisa; Ryuji Ohue-Kitano; Hiromi Takada; Mayu Yamano; Akari Nishida; Daiki Sasahara; Yuki Masujima; Keita Watanabe; Shota Nishikawa; Sakura Takahashi; et al. (Nature Communications)
Abstract Commensal bacteria affect host health by producing various metabolites from dietary carbohydrates via bacterial glycometabolism; however, the underlying mechanism of action remains unclear. Here, we identified Streptococcus salivarius as a unique anti-obesity commensal bacterium. We found that S. salivarius may prevent host obesity caused by excess sucrose intake via the exopolysaccharide (EPS) –short-chain fatty acid (SCFA) –carbohydrate metabolic axis in male mice. Healthy human donor-derived S. salivarius produced high EPS levels from sucrose but not from other sugars. S. salivarius abundance was significantly decreased in human donors with obesity compared with that in healthy donors, and the EPS–SCFA bacterial carbohydrate metabolic process was attenuated. Our findings reveal an important mechanism by which host–commensal interactions in glycometabolism affect energy regulation, suggesting an approach for preventing lifestyle-related diseases via prebiotics and probiotics by targeting bacteria and EPS metabolites.